The economics of international airline transport - Peoples, James (Advances in airline economics ;, 2014)
This volume provides in depth analyses of: changes in international air transportations legal environment; airline companies market behavior in this new environment; trade growth in response to changing airline market behavior; and examination of the external costs and benefits associated with growth in international air transportation.